Hadith #2944 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Mustward bin Shadad; Jubayr bin Nufayr al-Hadrami; Musa bin Mrwan موسى بن مروان (Sunan Abi Dawud)
‘Umar reported me to collect the sadaqah (i.e. zakat). When I became free, he ordered to give me payment for it. I said: I have worked for the sake of Allah. He said: Take what you have been given, for I held an administrative post in the time of the Messenger of Allah (ﷺ), and he gave me payment for it.
Grade: Sahih

Hadith #4879 - Sunan Abi Dawud - al-Mustward bin Shadad; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Makhul al-Shami/al-Damashiqi مكحول الشامي (Sunan Abi Dawud)
This tradition has also been transmitted by ‘Isa b. Abi ‘Isa al-sailahini from Abu al-Mughirah, as Ibn al-musaffa said.
Grade: Sahih